2015
DOI: 10.1007/s12149-015-1005-3
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-14 urea breath test: does it work in patients with partial gastric resection?

Abstract: The sensitivity of the standard C-14 UBT was very poor for patients with PGR, and results of HpSAT were superior in this population. Certain modifications are needed if C-14 UBT is to be used in PGR patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The best results were obtained when the breath samples were collected after 20 minutes and the threshold established > 35 counts per minute (CPM). 46 New tests were also developed: 1, the ammonia breath test showed different breath ammonia levels at baseline and after urea ingestion in 10 of the 14 H. pylori positive patients. Such tests could represent lower cost, 47 and 2, a new point-contact nanosensor device using salts of the organic conductor tetracyanoquinodimethane was assessed and could be used in a portable breath analyzer.…”
Section: Molecular Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best results were obtained when the breath samples were collected after 20 minutes and the threshold established > 35 counts per minute (CPM). 46 New tests were also developed: 1, the ammonia breath test showed different breath ammonia levels at baseline and after urea ingestion in 10 of the 14 H. pylori positive patients. Such tests could represent lower cost, 47 and 2, a new point-contact nanosensor device using salts of the organic conductor tetracyanoquinodimethane was assessed and could be used in a portable breath analyzer.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…Another study used the 14 C‐UBT in such patients. The best results were obtained when the breath samples were collected after 20 minutes and the threshold established > 35 counts per minute (CPM) …”
Section: Noninvasive Testsmentioning
confidence: 99%
“…Previous research has shown that the 14‐C urea breath test has a sensitivity of 0.96 and a specificity of 0.93; therefore, it remains the main method of H. pylori detection. The 14‐C urea breath test has high sensitivity and accuracy for patients’ status post‐partial gastrectomy …”
Section: Discussionmentioning
confidence: 99%